Formulasi Gel Nanostructured Lipid Carriers Ekstrak Akar Murbei (Morus alba L.) sebagai Pencerah Kulit pada Model Zebrafish - Faizatun, Faizatun; Murti, Irene Intan Permata (Faculty of Pharmacy, Universitas Pancasila, 2023)
Mulberry is a plant that has been shown to be effective as a whitening agent. The objective of this research was to evaluate the efficacy of mulberry root extract (MRE) and its nanostructured lipid carrier (NLC) extracts in terms of their ability to lighten skin tone by using zebrafish as a model. NLC were formulated into gel preparations. The whitening effect of MRE and NLC was evaluated, and the melanin content of the extracts was found to be the result of the evaluation. Based on the results of morphological observations, a decrease in melanin levels was seen in the eye. In the mulberry root extract, the melanin level decreased with an increase in the concentration of the mulberry root extract. In the NLC of mulberry root extract, a decrease in melanin levels was obtained at an increased NLC concentration of mulberry root extract. It can be concluded that mulberry root NLC has the ability to act as a whitening agent, which is distinguished by the reduction of melanin content.